Simple Field Storage of Fish Samples for Measurement of DNA Content by Flow Cytometry - Hubálek, Martin; Flajšhans, Martin (Cytometry. Part A, 2021)
Flow cytometry is an effective and widely used tool for determination of ploidy in fish, but it is not always possible to access the fresh samples for analysis. We investigated the potential for extended storage of fish tissue with sterlet and tench as representative species of Chondrostei and Teleostei, using blood and fin of subadult/adult specimens and tail of larvae. Thirteen procedures for extending storage, selected for rapidity and simplicity in both field and laboratory conditions, were tested for each tissue sample. Flow cytometry was applied to fresh tissue immediately after sampling and to tissue subjected to experimental protocols, always along with species-specific standard, after 1, 5, and 10 days storage at 0-4°C or freezing at -80°C. The fluorochrome 4',6-diamidine-2'-phenylindole dihydrochloride was used with excitation/emission maximum 358/461 nm. Based on the measurability of stored samples, evaluation of directly measured coefficients of variation of their DNA peaks and the changes in fluorescence intensity compared to fresh tissue, optimal procedures for extended storage of the selected tissue types of the model species are suggested. © 2020 The Authors. Cytometry Part A published by Wiley Periodicals LLC. on behalf of International Society for Advancement of Cytometry.
Keywords: Flow Cytometry; ploidie; fixation; blood; preservation; tench; coefficient of variation; fluorescence intensity; průtoková cytometrie; zvířata; larva tail tissue; Ploidies; fin tissue; DNA; sterlet; Animals